Kundun - Touchstone Pictures; Canal+ Image (Firm). ([Calif.] Touchstone Pictures, 1997)
In a remote area of Tibet a two-year-old child is identified as the Dalai Lama. The story follows him into adulthood where he tries to rule his nation at one of the most challenging times in its history.
Based on the life of His Holiness, the Dalai Lama.
Produced with the cooperation and contribution of His Holiness, the Dalai Lama.
A Cappa/de Fina production.
VHS.
Directed by Martin Scorsese ; written by Melissa Mathison ; produced by Barbara de Fina.
Keywords: Bstan-'dzin-rgya-mtsho -- Dalai Lama XIV -- 1935-.; Feature films; Dalai lamas -- Drama; Tibet (China) -- Drama